2015
DOI: 10.24059/olj.v19i3.672
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Online Curriculum Promoting Transformative Learning in Post Professional Doctoral Students

Abstract: Written reflections of 113 occupational therapy clinical doctoral students who graduated from an online program between 2007 and 2013 were analyzed for themes which reflected transformative learning and characteristics of curricular design which promoted transformative learning. Qualitative analyses of written reflections were performed. Several themes emerged which are presented using the framework of Person/Learner, Environment/Learning Context, and Occupation/Engagement in Learning Activities. Strategies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Research during this period also continued to focus on supportive mentoring practices, continuous support for doctoral students and sensitivity to cultural issues. In addition, the research also started to focus on curriculum design issues helping doctoral learners become transformational learners (Provident, Salls, Dolhi, Schreiber, Mattila, & Eckel, 2015).…”
Section: Evolution Of the Online Doctoral Research Environment Duringmentioning
confidence: 99%
“…Research during this period also continued to focus on supportive mentoring practices, continuous support for doctoral students and sensitivity to cultural issues. In addition, the research also started to focus on curriculum design issues helping doctoral learners become transformational learners (Provident, Salls, Dolhi, Schreiber, Mattila, & Eckel, 2015).…”
Section: Evolution Of the Online Doctoral Research Environment Duringmentioning
confidence: 99%
“…A scarcity of literature exists that examines the benefits of a POTD degree. Provident et al (2015) and Salls et al (2012) both had limited or small sample sizes from single source populations but noted that graduates of POTD programs reported personal and professional growth. Salls et al (2012) found that POTD graduates were more likely to utilize evidence-based practice (EBP) and reported increased familiarity with the use of scholarly writing, which helped them to overcome time constraint barriers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online Communication, Synchronous, and Asynchronous. Throughout the online education literature, it is documented that connection with faculty members in the online environment is vital to students' integration into learning communities (Provident et al, 2015;Rademaker et al, 2016), and teaching presence, with the associated social presence, can be supported online through the use of technology (Rockinson-Szapkiw, Baker, Neukrug, & Hanes, 2010). Ivankova and Stick (2007) conducted a mixed methods study, surveying 278 doctoral online students within Doctor of Education programs and following up with in-depth interviews.…”
Section: Program Factorsmentioning
confidence: 99%